2001
DOI: 10.1183/09031936.01.17406670
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of blood coagulation tests in lung cancer

Abstract: Previous studies have shown that activation of coagulation has an impact on the clinical course of lung cancer.This study was carried out to assess the potential prognostic significance of platelet count (P), prothrombin time (PT), partial thromboplastin time (PTT), anti-thrombin III (AT-III), fibrinogen (F), D-dimer (DD), factor II (F-II), factor VII (F-VII), factor X (F-X), protein C clotting (PCC), plasminogen (PL), and antiplasmin (AP) in 343 consecutive new lung cancer patients. A set of 32 anthropometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
72
2
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 27 publications
(32 reference statements)
5
72
2
3
Order By: Relevance
“…7 In addition, changes in the clotting/fibrinolytic system in lung carcinoma patients are common. 3,9,[11][12][13][14][15][16][17] Clinical and experimental evidence supports the idea that the activation of coagulation/fibrinolysis may play an important role in the invasiveness of cancer. 6,7 For example, Kwaan and Keer 6 demonstrated a correlation between coagulation changes and the natural history of malignancies.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…7 In addition, changes in the clotting/fibrinolytic system in lung carcinoma patients are common. 3,9,[11][12][13][14][15][16][17] Clinical and experimental evidence supports the idea that the activation of coagulation/fibrinolysis may play an important role in the invasiveness of cancer. 6,7 For example, Kwaan and Keer 6 demonstrated a correlation between coagulation changes and the natural history of malignancies.…”
Section: Discussionmentioning
confidence: 85%
“…16,17 In the earlier study, 16 we reported that several clotting tests were predictive of prognosis, according to both univariate and multivariate models. Univariate tests showed that low values of plasma PT, high values of F, and abnormally elevated concentrations of DD were associated significantly with an adverse outcome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations